Higher levels of cortisol, a biomarker of stress, among residents of municipalities with lower urban life quality index - Díaz Cavieres, Alejandro; Niemeyer, Hermann M. (Revista Chilena de Salud Pública, 2020)
Introduction: Socioeconomic and urban inequalities are associated with health in Santiago; nonetheless, the causal mechanisms underlying health inequalities are not entirely clear. This article quantifies the stress of individuals living in different municipalities and discusses its role as cause and consequence in the generation of health inequalities. The objective of this study was to determine the relationship between the Urban Quality of Life Index (UQoLI) of individuals’ municipality of residence in Santiago, Chile with their hair cortisol concentrations (HCC), a biomarker of chronic physiological stress. Materials and Methods: The relationship of HCC with age, sex and UQoLI was explored in a sample of 80 university students in Santiago, Chile. Results: No significant correlations were found between HCC and age and sex. A significant correlation was found between HCC and UQoLI, and significant differences were found be¬tween HCC at different levels of UQoLI (High, Average, and Low). Discussion: Results suggest that HCC differences could be considered a result of urban in¬equalities, as well as a possible cause of health inequalities. The role of stress should be inclu¬ded in public health policies, to expand support networks and prevent stress, especially among people living in areas with low urban quality of life.